1997
DOI: 10.1021/jp971965g
|View full text |Cite
|
Sign up to set email alerts
|

Qy-Excitation Resonance Raman Spectra of Chlorophyll a and Related Complexes. Normal Mode Characteristics of the Low-Frequency Vibrations

Abstract: Q y -excitation resonance Raman (RR) spectra are reported for film aggregates of chlorophyll (Chl) a and a series of related complexes. The latter include Mg(II) octaethylporphyrin (MgOEP), Mg(II) trans-octaethylchlorin (MgOEC), methyl-9-desoxomesopyrochlorophyllide (DMPChl) a, and methylpyrochlorophyllide (MPChl) a. These complexes represent a series in which the structural complexities of Chl a (saturated pyrrole ring, isocyclic ring, C9-keto group, C2-vinyl group, and C10-carbomethoxy group) are systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 66 publications
4
39
0
1
Order By: Relevance
“…33), which compares with the frequency of the breathing mode of the tetrapyrrole53 (Carles Curutchet, personal communication). In the case of the Chl b −a pair, it has been shown that a mode around 750 cm −1 is coupled to the electronic dynamics36 and this energy is close to the frequency of in-plane deformations of the pyrrole54. Furthermore, vibrational dephasing in chromophores55 and in other systems such as photoreceptors56 is known to be of the order of picoseconds.…”
Section: Resultsmentioning
confidence: 98%
“…33), which compares with the frequency of the breathing mode of the tetrapyrrole53 (Carles Curutchet, personal communication). In the case of the Chl b −a pair, it has been shown that a mode around 750 cm −1 is coupled to the electronic dynamics36 and this energy is close to the frequency of in-plane deformations of the pyrrole54. Furthermore, vibrational dephasing in chromophores55 and in other systems such as photoreceptors56 is known to be of the order of picoseconds.…”
Section: Resultsmentioning
confidence: 98%
“…Examples of photoinduced EnT and ET processes can be found in natural and artificial photosynthesis in which the light energy is collected by an array of chromophores and is transferred to a protein at a reaction center or electron donor-acceptor complexes through EnT, respectively, and in which sequential ET processes take place within a few picoseconds to milliseconds to produce charge-separation states at which the chemical potentials are generated. Although resonance Raman measurements attempt to address this issue, [16][17][18][19][20] the structural information obtained from those measurements is indirect. Moreover, intermediates that participate in bond formation or breakage are often excited states.…”
Section: Importance Of Excited State Structural Informationmentioning
confidence: 99%
“…Which vibrational modes are most responsible for the photochemical reactions? Although resonance Raman measurements attempt to address this issue, [16][17][18][19][20] the structural information obtained from those measurements is indirect. While m D, m A and R DA can be obtained by measuring steadystate structures of the reactants in photoinduced EnT and ET reactions, [21] these measurements may not be feasible for fast and reversible processes in most of the photochemical and photophysical reactions when the excited state adopts a different structure from that of the ground state.…”
Section: Importance Of Excited State Structural Informationmentioning
confidence: 99%
“…[7] Es wurden umfangreiche experimentelle und theoretische Studien zum Einfluss des Donor-Acceptor-Abstandes, der Reorganisationsenergie, des Reaktionsmediums und anderer Faktoren auf die Geschwindigkeitskonstanten durchgeführt. [8][9][10][11][12][13][14][15] [16][17][18][19][20] die aber nur indirekte Strukturdaten liefern. m D , m A und R DA können zwar durch Untersuchung stationärer Strukturen in photoinduzierten Energie-und Elektronentransferreaktionen gewonnen werden, [21] diese Messungen sind aber bei schnellen, reversiblen photochemischen oder photophysikalischen Prozessen meist nicht möglich, wenn sich die Strukturen von angeregtem und Grundzustand unterscheiden.…”
Section: Die Bedeutung Von Strukturdaten Von Molekülen In Angeregten unclassified